Radiology fundamentals : introduction to imaging & technology - Neutze, Janet A.; Singh, Harjit (Springer New York, 2012)
Radiology Fundamentals is a concise introduction to the dynamic field of radiology for medical students, non-radiology house staff, physician assistants, nurse practitioners, radiology assistants, and other allied health professionals. The goal of the book is to provide readers with general examples and brief discussions of basic radiographic principles and to serve as a curriculum guide, supplementing a radiology education and providing a solid foundation for further learning.  Introductory chapters provide readers with the fundamental scientific concepts underlying the medical use of imaging modalities and technology, including ultrasound, computed tomography, magnetic resonance imaging, and nuclear medicine. The main scope of the book is to present concise chapters organized by anatomic region and radiology sub-specialty that highlight the radiologist's role in diagnosing and treating common diseases, disorders, and conditions. Highly illustrated with images and diagrams, each chapter in Radiology Fundamentals begins with learning objectives to aid readers in recognizing important points and connecting the basic radiology concepts that run throughout the text. It is the editors' hope that this valuable, up-to-date resource will foster and further stimulate self-directed radiology learning-the process at the heart of medical education.